2017
DOI: 10.3892/ol.2017.6380
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin induces apoptosis in vitro through suppressing the MAPK and PI3K signaling pathways in gastric cancer

Abstract: Luteolin, an active component of traditional Chinese medicine, exhibits potential for anti-tumor proliferation; however, the molecular events occurring in such process and the signal transduction pathways involved are currently unknown. Our group previously reported that luteolin inhibited proliferation and induced apoptosis in the gastric cancer cell line BGC-823. The aim of the present study was to investigate the mechanism by which the mitogen-activated protein kinase (MAPK) and phosphatidylinositol-4,5-bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 73 publications
1
30
0
1
Order By: Relevance
“…LUT exerts cytoprotective effects against lipid peroxidation products and led to apoptosis of PC12 cells by inducing the phosphorylation of ERK1/2, JNK, and P38 MAPK signal transduction [27]. Moreover, it induced apoptosis by inhibiting PI3K/AKT and ERK1/2 MAPK intracellular signaling and increasing the levels of apoptotic proteins in gastric cancer BGC 823 cells [28]. Moreover, LUT was shown to function as an enhancer, sensitizing cells to doxorubicin-induced autophagy signaling in human osteosarcoma cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…LUT exerts cytoprotective effects against lipid peroxidation products and led to apoptosis of PC12 cells by inducing the phosphorylation of ERK1/2, JNK, and P38 MAPK signal transduction [27]. Moreover, it induced apoptosis by inhibiting PI3K/AKT and ERK1/2 MAPK intracellular signaling and increasing the levels of apoptotic proteins in gastric cancer BGC 823 cells [28]. Moreover, LUT was shown to function as an enhancer, sensitizing cells to doxorubicin-induced autophagy signaling in human osteosarcoma cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…Stevia pilosa and Stevia eupatoria extracts have compounds such as luteolin, quercetin, β-sitosterol, stigmasterol [11], seco-triterpenes [17], and longipinenes [18]. Luteolin has shown cellular arrest and apoptosis induction in many types of cancer cell lines, such as prostate cancer (PC-3), liver cancer (SMMC7721), colon cancer (COLO205), and cervical cancer (HeLa) [19]. Quercetin decreases the viability and proliferation of MCF-7 breast cancer cells through apoptosis activation, via increasing the levels of Bcl-2-associated X protein (BAX) and caspase-3 expression and decreasing Bcl-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The Consulting the literature showed that the phenolic acid components chlorogenic acid (Xue et al, 2017;Shao, Zhang, Chen, & Sun, 2015) and caffeic acid (Brautigan, Gielata, Heo, Kubicka, & Wilkins, 2018), and the flavonoids scutellarin (Nie et al, 2018;Sun et al, 2018;Tang & Gao, 2019), isoorientin (Huang, Jin et al, 2018;Lin et al, 2016), isovitexin (Lv, 2018), scutellarein (Jiang et al, 2018;Lu, Li, Li, & Asia, 2017;Zheng et al, 2017), luteolin (Niu, Guo, Gan, Bao, & Ren, 2015) and apigenin (Bhattacharya et al, 2018;Masuelli et al, 2017;Cai et al, 2011) had different degrees of inhibition on tumor cells. Among them, caffeic acid, isoorientin, isovitexin, luteolin and apigenin had better antiliver tumor activities.…”
Section: Analysis Of Migration Components In Plasmamentioning
confidence: 99%